Comparison Of Naproxen And Diacerein In The Treatment Of Knee Joint Osteoarthritis - Munir, Mehtab; Khan, Ayesha; Sayyar, Tauseef; Mufti, Maria; Siddiqui, Iqra; Abbasi, Sara Tariq (Journal of Rawalpindi Medical College, 2023)
Background: Knee osteoarthritis is a common disease in older age. Pain and limitation of movement are the main symptoms of knee osteoarthritis. Many pharmacological options are available for symptomatic relief but NSAIDs are mostly prescribed. Diacerein is also prescribed for osteoarthritis but data regarding its efficacy is still controversial. Moreover, studies regarding the comparison of diacerein with NSAIDs are deficient in Pakistan. Objective: The objective of the study was to compare the clinical efficacy of naproxen (NSAID) with diacerein in treating knee osteoarthritis. Methodology: Patients fulfilling inclusion criteria were included in the study. After written informed consent 60 patients of knee osteoarthritis were included in the study. They were divided randomly into two groups. Group A (n=30) was prescribed with tablet naproxen 500mg twice daily and group B (n=30) was given capsule diacerein 50mg twice daily for 12 weeks. Baseline VAS and WOMAC scores of the patients were noted. These scores were compared with scores achieved 12 weeks after intervention. Intra-group comparison of the scores was also carried out. SPSS version 23.0 was used for statistical analysis. Results: WOMAC and VAS scores comparison of the two groups (A & B) before intervention showed an insignificant p-value that is 0.815 for the WOMAC score and 0.509 for the VAS score. After intervention means WOMAC score i.e.10.50 ± 2.46 of group A (treated with naproxen) was better than the mean 29.62 ± 7.03 of group B (treated with diacerein) showing significant p-value (< 0.001). Similarly mean VAS of group A 1.92 ± 0.58 improved more than the mean VAS of group B i.e 3.38 ± 0.75 with significant p-value (< 0.001). Intra-group comparison of the groups also showed a significant p-value. Conclusion: Clinical efficacy of naproxen is better than diacerein in treating knee osteoarthritis.